Attention Economy in Video Streaming Application: Avatar Interaction in YouTube Video Content Monetization - Maharso, Reno Dalu; Irwansyah, Irwansyah (UI Scholars Hub, 2019)
This article would like to unveil avatar interactions under the attention economy framework in online video streaming applications, taking YouTube as example, and how it benefits content creators to monetize their channels’ contents. The theory of attention economy is proposed to explain how these avatar interactions in video streaming applications are perceived as a mode of transaction by using attention as universal currency. This article is elaborated using the social information processing theory to identify content creators’ avatar credibility through the application of cues during computer-mediated communication. To enrich the concept of credibility and methodology, the prominence-interpretation theory is also proposed. The method applied to this study is qualitative content analysis by examining five monetized Indonesian YouTube channels. In coding stage, several elements of the channels were identified, such as channel age, number of followers, and number of videos. Then from each channel, the video with the biggest number of views was picked and the types of advertisement showing up in such videos were examined. The observation found that five biggest YouTube channels in Indonesia in terms of number of subscribers had monetized their videos. Their videos had either overlay or non-stoppable video ad content during playback. This showed that number of views and engagements were generated from interactions between the content creators’ and visitors’ avatars. Attention metrics served as metrics in the attention economy framework, which in turn contribute to monetization — making it possible to see that YouTube channels were standardized to meet advertisers’ requirements.